Micro- and Nano-Plastic-Induced Adverse Health Effects on Lungs and Kidneys Linked to Oxidative Stress and Inflammation - Seung Eun Lee; Do Yun Kim; Taek Seung Jeong; Yong Seek Park (Life)
Micro- and nano-plastics (MNPs) are small plastic particles that result from the breakdown of larger plastics. They are widely dispersed in the environment and pose a threat to wildlife and humans. MNPs are present in almost all everyday items, including food, drinks, and household products. Air inhalation can also lead to exposure to MNPs. Research in animals indicates that once MNPs are absorbed, they can spread to various organs, including the liver, spleen, heart, lungs, thymus, reproductive organs, kidneys, and even the brain by crossing the blood–brain barrier. Furthermore, MPs can transport persistent organic pollutants or heavy metals from invertebrates to higher levels in the food chain. When ingested, the additives and monomers that comprise MNPs can disrupt essential biological processes in the human body, thereby leading to disturbances in the endocrine and immune systems. During the 2019 coronavirus (COVID-19) pandemic, there was a significant increase in the global use of polypropylene-based face masks, leading to insufficient waste management and exacerbating plastic pollution. This review examines the existing research on the impact of MNP inhalation on human lung and kidney health based on in vitro and in vivo studies. Over the past decades, a wide range of studies suggest that MNPs can impact both lung and kidney tissues under both healthy and diseased conditions. Therefore, this review emphasizes the need for additional studies employing multi-approach analyses of various associated biomarkers and mechanisms to gain a comprehensive and precise understanding of the impact of MNPs on human health.